Evaluation of Human Peroxisome Proliferator-Activated Receptor (PPAR) Subtype Selectivity of a Variety of Anti-inflammatory Drugs Based on a Novel Assay for PPARδ(β) - Hitoshi Kojo; Masao Fukagawa; Kaoru Tajima; Akiko Suzuki; Takao Fujimura; Ichiro Aramori; Ken-ichi Hayashi; Shintaro Nishimura (Elsevier, 2003)
ABSTRACT: The nuclear receptor PPAR (peroxisome proliferator-activated receptor) has three subtypes named α, δ(β), and γ that may act as receptors for a range of compounds including antihyperglycaemic drugs, insulin sensitizers, and non-steroidal anti-inflammatory drugs (NSAIDs). Although profiling of the subtype selectivity of the compounds for PPAR is indispensable to elucidate their pharmacological action, the absence of an appropriate transactivation assay for PPARδ led us to develop a sensitive and reproducible method. We found that co-expression of PPARδ, retinoid X receptor (RXR) α, and coactivators such as CBP and SRC-1 enhanced basal and agonist-dependent activation of PPAR responsive element (PPRE)-driven transcription by PPARδ, rendering a PPRE-driven reporter assay reliable and sensitive. Utilizing this assay for PPARδ, we re-evaluated the subtype selectivity of a variety of anti-inflammatory drugs for human PPAR. The PPAR agonists tested included two leukotriene (LT) D4 antagonist, seven NSAIDs, and two anti-rheumatoid drugs. We found that a novel LTD4 antagonist, FK011 ([2-(((2-(4-tert-butyl-1,3-thiazol-2-yl)-1-benzofuran-5-yl)oxy)methyl)phenyl]acetic acid), showed marked agonistic activity for PPARγ. NSAIDs were classified into the following three groups: those showing no activity for all subtypes, those that were selective for PPARγ such as indomethacin and diclofenac, and those showing agonistic activity for the δ and γ subtypes such as ibuprofen. These results will be important to studies on the molecular mechanisms of pharmacological actions of LTD4 antagonists and NSAIDs.